The 1970s General Education Act by means of images - Comas Rubí, Francisca; Sureda Garcia, Bernat (Historia y Memoria de la Educación, 2021)
The aim of this paper is to provide an approach to the graphic representation of the Ley General de Educación (LGE) and the discourses it has generated. To this end, a distinction is made between the official or public image and its means and times of projection, and the private images that make up the iconic legacy of this legislative reform from its beginning to the present day. This approach shows that the graphic representation of the LGE, comparing the official and public image with the private one, leads to different and sometimes opposing narratives, which show the complex reality in which this ambitious educational reform was conceived and applied.